MENAKAR KEBERAGAMAAN MASYARAKAT DAN SOLIDARITAS MEMBANGUN MASJID (STUDI KASUS MASJID DARUL HIDAYAH KELURAHAN DASAN CERMEN KECAMATAN SANDUBAYA KOTA MATARAM) - Naamy, Nazar (KOMUNITAS, 2017)
Religiousness is the knowledge level, belief, realization and full of comprehension of a person for the religion teachings which he believes, or an attitude of surrender to an existing strength outside of himself embodied in the activities and individual behavior in everyday life which include five dimensions: religious beliefs, worship, religion practice, religious knowledge, full of comprehension, and religious practice. The main problems in this research are: How is the understanding of Islam in the community of DasanCermen Village, Sandubaya Sub-district, Mataram City? How is practice of the teachings of Islam in the community of DasanCermen Village, Sandubaya Sub-District, Mataram City? What do factors influence people’s spirit in building DarulHidayah mosque in DasanCermen village, Sandubaya Sub-district, Mataram City? The purpose of this research is to analyze the religiousness level of Dasan Cermen community and solidarity to build a mosque by using the sociology theory of Emile Durkheim. The type of this research was field study (field research) and the method used was qualitative data analysis that is analytic descriptive. This research also used phenomenology approach which included: daily activities of society, talks directly or indirectly, forms of religious activity, and intensity of society in the utilization of mosques. From the study conducted, this research found that the factors which encourage the DasanCermen community to build a mosque is a factor of ideology of rewardfrom Allah, a good collective solidarity passed down through the rural society, written rules and on the demands of sodakoh of road users who are so enthusiastic for the establishment of Darul Hidayah mosque. In addition, the DasanCermen community already has a mechanical solidarity to ideology in building a mosque. Although DasanCermen community is urban society, solidarity in building mosque is seen from the ideology of their religious understanding. This ideology also evolved as their mechanical solidarity as a rule which has been passed down from its predecessors, because the people still have a solid communal life in which the citizens have same interests and same awareness.